Seasonal Variation in Rooting Behaviour of Ginkgo biloba L. Cuttings - Bhattarai, Nabin; Joshi, Sanu Devi (Journal of Natural History Museum, 2015)
Propagation by cuttings is an effective method for ex-situ conservation of plants. In the present study, propagation of Ginkgo biloba L. was conducted using hardwood and semi hard wood cuttings. The cuttings from basal part of the tree were selected for the experiment and planted during rainy (i.e. July) and summer season (i.e. April) at Central Department of Botany, T.U. Cuttings beds were prepared using 3:1 sand and soil. Different concentration of auxins such as IAA, NAA and IBA were found effective in inducing rooting. During July, the stem cuttings treated with 1000 ppm IAA for 30 minutes induced highest percentage (90 %) and statistically signifi cant (P< 0.05) rooting while those treated with same concentration and time induced only 40% rooting during April. Like wise other auxins NAA and IBA induced more rooting during July and less rooting during April. Cuttings planted as control, during July showed 10 % rooting while during April did not show any rooting. Among all the auxins studied, IAA hormone and rainy season was found to be the most effective for rooting of G. biloba cuttings. From the anatomical study it was revealed that vascular cambium, secondary phloem, cortical cells and pericycle cells took part on rooting. Successfully rooted cuttings were then transferred to the natural soil condition. J. Nat. Hist. Mus. Vol. 26, 2012: 175-180